Pengaruh profitabilitas, ukuran perusahaan dan pertumbuhan perusahaan dalam memprediksi kondisi financial distress - Astria, Indria Sri; Norisanti, Nor; Mulia Z, Faizal (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2023)
This study aims to analyze the influence of profitability, company size and company growth in predicting financial distress in the property and real estate sub-sectors. The data was selected using a purposive sampling method and there were 10 companies listed on the Indonesia Stock Exchange from 2020-2022 which were the research samples. This study uses the normality test, the coefficient of determination, the multiple correlation test, the f test and the T test. To analyze the data, the results indicate that the company's profitability and growth have an influence on financial distress. Meanwhile, Company Size has no effect on Financial Distress.